Structural Response and Optimization of a Tugboat Midship Section Under Varied Transverse Frame Spacing Using Finite Element Analysis - Amalia Ika Wulandari; Alamsyah Alamsyah; Hariyono; Ryan Raruk; Husein Syahab; Muhammad Anjas Syam; Suardi Suardi; Dimas Fajar Prasetyo (Naval Architecture Department, Kalimantan Institut of Technology, 2026)
Transverse framing systems serve as a critical structural backbone for marine vessels, governing localized stiffness and cross-sectional hull strength. This study investigates the structural response of a tugboat’s midship section under various transverse frame spacing configurations using the Finite Element Method (FEM) to optimize lightweight tonnage (LWT) while maintaining seaworthiness. Utilizing structural data from a under-30-meter service tugboat, five distinct frame spacing variations 500 mm (baseline actual design), 550 mm, 575 mm, 600 mm, and 625 mm were modeled using four-node shell elements (SHELL181) within ANSYS software. A constant uniform static deck pressure load of 0.0122 MPa was applied to evaluate localized stress distributions and elastic displacement fields under rigid boundary conditions. Numerical simulations reveal a progressive, linear increase in both equivalent stresses and vertical deflections as the unsupported span of the deck plating expands. The maximum von Mises equivalent stress escalated from 31.4237 MPa at the 500 mm baseline configuration to 34.1552 MPa (550 mm), 35.4687 MPa (575 mm), 36.8590 MPa (600 mm), and peaked at 40.6607 MPa under the widest 625 mm spacing. Concurrently, the total displacement vector sum rose from 0.56047 mm at the baseline to a peak of 0.86030 mm at 625 mm spacing due to the reduction of localized flexural rigidity. Crucially, despite the elevated structural responses, all configurations safely satisfy the strict structural limits enforced by the Indonesian Classification Bureau (BKI 2022) rules, as the maximum peak stress (40.6607 MPa) remains substantially below the nominal upper yield strength of ordinary hull structural steel (ReH = 235 N/mm2). These findings demonstrate that extending the transverse frame spacing up to 625 mm is structurally viable, offering a verified mechanism for weight optimization without compromising structural safety margins.